2015
DOI: 10.1145/2721896.2721899
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Opportunistic Networks with Legacy Nodes

Abstract: Mobile opportunistic networking utilizes device-to-device communication to provide messaging and content sharing mechanisms between mobile users without the need for supporting infrastructure networks. However, enabling opportunistic networking in practice requires a sufficient number of users to download, install, and run the respective routing and application software to provide sufficient node density, and thus connectivity for the network to actually function. In this paper, we explore reaching out to node… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Ref. [38] follows the "gateway-based" structure to make the contents inside DTN accessible to users who are not DTN-aware by leveraging shared access points as gateway nodes. Taken together, in this work, we adopt the "gateway-based" approach, for reasons that, firstly, from the perspective of implementation the least effort is required for modification on existing functionalities of clients and servers; secondly, little knowledge about DTN is requisite for users; thirdly, the isolation of DTN makes the system more general-purpose, extensible, and flexible.…”
Section: Bridging Dtn With Http-based Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. [38] follows the "gateway-based" structure to make the contents inside DTN accessible to users who are not DTN-aware by leveraging shared access points as gateway nodes. Taken together, in this work, we adopt the "gateway-based" approach, for reasons that, firstly, from the perspective of implementation the least effort is required for modification on existing functionalities of clients and servers; secondly, little knowledge about DTN is requisite for users; thirdly, the isolation of DTN makes the system more general-purpose, extensible, and flexible.…”
Section: Bridging Dtn With Http-based Servicesmentioning
confidence: 99%
“…Taken together, in this work, we adopt the "gateway-based" approach, for reasons that, firstly, from the perspective of implementation the least effort is required for modification on existing functionalities of clients and servers; secondly, little knowledge about DTN is requisite for users; thirdly, the isolation of DTN makes the system more general-purpose, extensible, and flexible. Although the basic idea of our work bears some resemblance to [38], in our design, the gateway nodes are not specialized APs, but ordinary human-carried or vehicle-mounted devices instead. Apart from the three typical models, aiming at rendering support for a wider range of applications with a unified bottom layer, Ref.…”
Section: Bridging Dtn With Http-based Servicesmentioning
confidence: 99%
“…A related question is if web users moving between access points would also contribute to the connectivity of a disconnected ICN. We have shown that they can make a difference if the Liberouter nodes instrument the web storage of mobile browsers for relaying messages [35].…”
Section: Validationmentioning
confidence: 99%